Effects of limiting environmental conditions on functional traits of Hedera helix L. vegetative shoots - Blinkova, Olena; Rawlik, Katarzyna; Jagodziński, Andrzej M. (Frontiers in Plant Science, 2024)
Hedera helix L. is a widespread liana that significantly influences forest ecosystems in temperate zones. In this study, it was confirmed that H. helix dominates the herbaceous layer of the Kórnik Arboretum, with clear links between its above-ground biomass and key environmental factors. The study revealed that, under intense soil shading, the leaf-to-stem biomass ratio was disproportional, favoring leaves. Leaf and stem water content reflected the plant's adaptation to soil moisture, aligning with its field capacity. Strong relationships were found between leaf water content and soil moisture, while the correlations between leaf water content and soil light variability were weaker. The study also confirmed positive relationships between daily light integral and leaf water content, with a less pronounced effect on stem water content.